Analysis of ceramic product quality: A Six Sigma approach - Ridwan, Asep; Sonda, Atia; Zilardhi, Athariq (Universitas Sultan Ageng Tirtayasa, 2024)
In the industrial world, the quality and productivity of products play a crucial role in the success of various production systems. The ceramic industry encounters challenges related to defective products due to various factors. When COVID-19 struck, one ceramic tile company temporarily laid off workers and suspended operations at several plants due to a decrease in orders. In January 2023, the company only opened three plants. It was found that many problems were encountered particularly with the production of SL-type ceramic tiles (25 cm × 25 cm). They were still striving to reduce these issues and ensure smooth production processes. The problems that frequently occur can be attributed to the production process, materials, machinery, or human factors. Consequently, research has been conducted to control defective products, thereby enhancing production quality using the Six Sigma DMAIC method. The DMAIC methodology is the cornerstone of Six Sigma problem-solving, involving sequential improvement steps. These steps in the DMAIC method include Define, Measure, Analyze, Improve, and Control. Based on the conducted calculations, an average DPMO (Defects per Million Opportunities) value of 8621.2 was obtained, with an average sigma value of 3.91. DPMO, which measures failure in the DMAIC method, indicates failures per million opportunities. Based on this, it suggests that production falls within the average category of the Indonesian industry and is deemed sufficiently satisfactory. This study also provides improvement steps that need to be taken to reduce defective products.